2008
DOI: 10.1159/000113792
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Analysis of Cell Cycle Regulators in Urothelial Bladder Cancer Identifies p16 and p27 as Potentially Useful Prognostic Markers

Abstract: Aims: We investigated the value of multiple cell cycle markers for their prognostic impact on overall survival and recurrence-free survival in urothelial carcinoma (UC). Methods: A tissue microarray consisting of 99 UCs was evaluated for the expression of p53, p16, p21, p27, cyclin D1, cyclin E , Bcl-2, Ki-67 and PCNA. Statistical analysis was performed applying Kaplan-Meier and Cox regression models using receiver operator characteristic curves for determination of markers’ cutoffs. Results: Expression above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 71 publications
3
13
1
Order By: Relevance
“…The most challenging task in molecular analysis of bladder cancer is to establish the clinical relevance of each molecular subgroup with respect to various tumor characteristics, beyond the histologic appearance. A variety of molecular markers, such as cell cycle regulators [18][19][20], cell proliferation promoters [21], signal transduction factors [22,23], apoptosis modulators [24,25], extracellular matrix-modulating molecules [26,27], and angiogenesis regulators [28,29], have been found to be associated with tumor grade and staging [13,30], risk of recurrence [29,31,32], and progression [33].…”
Section: Overview: Technical Approaches To the Molecular Pathways Of mentioning
confidence: 99%
“…The most challenging task in molecular analysis of bladder cancer is to establish the clinical relevance of each molecular subgroup with respect to various tumor characteristics, beyond the histologic appearance. A variety of molecular markers, such as cell cycle regulators [18][19][20], cell proliferation promoters [21], signal transduction factors [22,23], apoptosis modulators [24,25], extracellular matrix-modulating molecules [26,27], and angiogenesis regulators [28,29], have been found to be associated with tumor grade and staging [13,30], risk of recurrence [29,31,32], and progression [33].…”
Section: Overview: Technical Approaches To the Molecular Pathways Of mentioning
confidence: 99%
“…To the best of our knowledge, this is the first study using post-PCR RLB hybridization technique for HPV-DNA detection in FFPE bladder cancer tissue. HPV was detected most frequently in low-grade carcinoma [20] which can be explained by the different biologic pathways in the carcinogenic process of non-muscle invasive versus invasive bladder cancer: While low-grade cancer is associated with chromosome nine allelic loss and p16 overexpression, high-grade and invasive carcinoma is linked to lack of p16 expression and p53 mutation [20][21][22]. Therefore, we focused on NMIBC samples in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one investigation demonstrated that CDH1 (E-cadherin) expression is an individual predictor of time to recurrence in grade 1-2 NMIBC tumours [19], although this finding could not be confirmed in the present study. PCNA expression is a measure of the rate of tumour proliferation and increased recurrencefree survival has been observed in patients with high-grade tumours expressing PCNA [24].…”
Section: Discussionmentioning
confidence: 99%
“…These authors observed similar variability in EGFR staining in other tumour forms as well. Moreover, there are no standardized cut-off levels for altered expression of proteins, and some investigators even determine optimal cutoff values by employing receiver operator characteristic (ROC)-based methods after the analysis has been conducted [24].…”
Section: Discussionmentioning
confidence: 99%